Seeking online telemedicine abortion outside the jurisdiction from Ireland following implementation of telemedicine provision locally. Issue 4 (25th October 2021) - Greene, Jo; Butler, Éadaoin; Conlon, Catherine; Antosik-Parsons, Kate; Gomperts, Rebecca
Abstract : Background: Abortion was legalised in Ireland in 2019 and telemedicine provision introduced in April 2020. We examined patterns in and reasons for seeking and receiving online telemedicine abortion outside the jurisdiction following legalisation and introduction of telemedicine abortion. Methods: Quantitative analysis compared frequency of contact, completed requests, service user characteristics and reasons for contacting Women on Web (WoW). Statistical analyses assessed if COVID-19 restrictions and the implementation of telemedicine abortion locally impacted on WoW contact patterns. Thematic analysis of email correspondence analysed reasons for seeking online telemedicine abortion. Results: There were 764 requests from Ireland to WoW in 2019–2020, with 225 (29.5%) completed. Requests declined by 90 (21%) between 2019 and 2020, and proportion of completed requests declined by 11.3% (n=70). During COVID-19 restrictions, the proportion of completed requests decreased even more (25%, n=24). Legal restrictions and cost declined as reasons for seeking online telemedicine and childcare, work/study commitments and being with partner/friend increased. During COVID-19 an abusive partner increased as the cited reason. Barriers cited in email correspondence included lack of proximate provider, not qualifying due to legal status and difficulty participating in consultations due to an abusive partner. Conclusions: Online telemedicine abortion seeking from WoW outside the jurisdiction reduced in the second year of legalisation. Local introduction of telemedicine abortion addressed reasons cited for seeking online telemedicine, other than abusive partner. Increasing awareness of abortion provision, particularly access pathways, free cost and confidentiality, promoting normalisation and retaining local telemedicine can reduce reliance on online telemedicine. Extending the format of local telemedicine abortion to include text-based contact could alleviate how an abusive partner impedes access.